Analysis Of Voice Data Security Security By Using The Rc4 Algorithm - Rika Nurhidayati; Salauddin Muis (SEAN Institute, 2021)
Data security and confidentiality is one of the most important aspects in the field of communication, especially communication using computer media. One of the fields of science that is used to secure data is cryptography. Cryptography is a science that uses mathematical equations to encrypt and decrypt data. Encryption is the process of converting plaintext (readable data) into ciphertext (unreadable data) and decryption is the opposite of encryption, which changes ciphertext back into plaintext. In this study, the RC4 algorithm will be discussed to encrypt and decrypt mp3 files stored on the computer.